Metatarsal osteotomies for treating neuropathic diabetic foot ulcers - Yammine, Kaissar (2018)
Diabetic foot ulcers (DFUs) are usually treated with conservative management based on debridement, topical agents, and nonsurgical off-loading; however, the recurrence rate following such standard care is reported to be high. In the case of recalcitrant or recurrent ulcers, a surgical off-loading technique such as the metatarsal osteotomy (MO) is indicated. Thus, the aim of this study is to conduct a meta-analysis evaluating the efficacy of MO in treating DFUs. Four relevant studies were identified, including 119 patients with 129 DFUs; all wounds were refractory to a previous conservative treatment of a mean duration of 10.9 ± 4.2 months. With a mean follow-up period of 18.2 ± 5.7 months, the weighted pooled rates were as follows: 98.7% for ulcer healing (in a mean time to heal of 6.5 ± 1.2 weeks), 4.3% for ulcer recurrence, 10.3% for ulcer transfer, 3.7% for infection, and 3.4% for nonunion. These findings were found to be noticeably better than those reported in the literature following standard care, whether associated or not to nonsurgical off-loading methods and that for all the studied outcomes. Knowing the dismal natural history of recalcitrant DFUs treated conservatively, the results of the MO techniques seems to offer a promising alternative in terms of ulcer healing and ulcer complications. In addition to complicated wounds, the indications for MO could include noncomplicated ulcers with healing delay.